Association Between the Number of Intratympanic Steroid Injections and Hearing Recovery in Sudden Sensorineural Hearing Loss - Wang, Yixu; Gao, Ge; Wang, Le; Ma, Xin; Yu, Lisheng; Ye, Fanglei (Frontiers in Neurology, 2021)
The frequency of intratympanic (IT) steroid injection varies from once daily to once weekly or less among studies and does not reach a uniform standard. This study investigated the potential association between the number of IT steroid injections and hearing recovery to determine the optimal number in sudden sensorineural hearing loss (SSNHL) patients. A retrospective study involving 233 SSNHL patients receiving IT steroids plus batroxobin within 7 days of onset was performed. Patients were followed up for 3 months. More than 15 dB of HL improvement in the pretreatment pure tone average (PTA) was defined as effective. The effective group had a higher IT injection numbers than the ineffective group (≥ 6 times: 84.6 vs. 61.1, p < 0.001). Regardless of the unadjusted model or adjusted model, patients who received more frequent IT steroid injections seemed more likely to recover hearing (unadjusted model, OR, 95% CI: 1.25, 1.06–1.48; p = 0.007; adjusted model, OR, 95% CI: 1.21, 1.01–1.45; p = 0.044). Six IT injections had the highest rate of hearing recovery (79.1%). In conclusion, IT injection number was an independent factor that was positively associated with hearing recovery, and the optimal number of IT steroid injections was 6. Batroxobin plus higher number of IT steroid injections showed more effective for treating SSNHL.